Analysis of Factors that Affect Digital Investment Interest: A Study on Livin’ by Mandiri Users - Nirvani Nirvani; Liestyaningrum Rahmadhani Wisnu Putri (Transpublika Publisher, 2025)
This research examines how financial knowledge, accessibility, and trustworthiness affect people's interest in digital investing through the Livin' by Mandiri mobile application. Given the growing popularity of digital investment platforms, there's a clear need to understand what motivates public engagement with digital investment options. The study employed a quantitative methodology using causal associative research design and purposive sampling to survey 150 active Livin' by Mandiri users. Data collection was conducted via questionnaires, with multiple linear regression analysis used to evaluate the relationships between variables. Findings revealed that financial knowledge, accessibility, and trustworthiness all positively and significantly impact investment interest, both individually and collectively. With a determination coefficient of 78.9%, these three factors substantially account for the variation in investment interest levels. The results validate the application of Theory of Planned Behavior within digital investment contexts and offer practical insights for developing digital banking services that prioritize user-friendliness, security, and financial education.